Adapting Product Backlog Management Strategies: The Influence of Agile Communication Platforms in a Post-COVID World - Ohri, Samir (Digital Repository of Theses, 2025)
The transition to remote and hybrid work models has transformed the operational dynamics of Agile workflows, demanding innovative adaptations to maintain efficiency and collaboration. This dissertation identifies a critical gap in existing literature concerning integrating communication tools, stakeholder engagement, and organizational structures in product backlog management within virtual settings. The research aims to evaluate the influence of agile communication platforms on workflow efficiency in the post-COVID era. Employing a structured survey of 467 agile practitioners, the study utilizes MANOVA, Chi-square tests, and Structural Equation Modeling (SEM) to analyze relationships between communication methods, stakeholder roles, and tool utilization. Key findings reveal that while real-time and asynchronous communication tools are valued, virtual meetings often suffer from technical and structural inefficiencies, further exacerbated by time zone challenges. Additionally, inconsistent stakeholder engagement emerged as a primary barrier to practical backlog refinement, underscoring the need for structured feedback mechanisms and defined roles. The study also highlights the underutilization of integration tools despite their potential to streamline workflows and improve cross-team coordination. Concluding with actionable recommendations, the dissertation advocates optimizing virtual meeting protocols, standardizing feedback processes, and enhancing tool integration to bolster team alignment and adaptability. Future research should explore the longitudinal impact of evolving digital tools and hybrid frameworks on agile practices to enrich the field further. These findings contribute to advancing the understanding of agile methodologies in modern, distributed work environments.